2017
DOI: 10.1063/1.4974261
|View full text |Cite
|
Sign up to set email alerts
|

A practical approach to the sensitivity analysis for kinetic Monte Carlo simulation of heterogeneous catalysis

Abstract: Lattice kinetic Monte Carlo simulations have become a vital tool for predictive quality atomistic understanding of complex surface chemical reaction kinetics over a wide range of reaction conditions. In order to expand their practical value in terms of giving guidelines for the atomic level design of catalytic systems, it is very desirable to readily evaluate a sensitivity analysis for a given model. The result of such a sensitivity analysis quantitatively expresses the dependency of the turnover frequency, be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The reduced version of the model employed here was introduced by Gelß et al 41 and is obtained by excluding all processes involving br sites. It has been shown that chemical kinetics is mainly controlled by the cus sites [42][43][44] and that the reduced model reproduces the results of the full model quantitatively for many reaction conditions. 41 Being computationally cheap, the reduced model can be evaluated for a large number of different input parameter values, which makes it a valuable test problem for our interpolation method.…”
Section: B Realistic 1p-kmc Based Datamentioning
confidence: 91%
See 2 more Smart Citations
“…The reduced version of the model employed here was introduced by Gelß et al 41 and is obtained by excluding all processes involving br sites. It has been shown that chemical kinetics is mainly controlled by the cus sites [42][43][44] and that the reduced model reproduces the results of the full model quantitatively for many reaction conditions. 41 Being computationally cheap, the reduced model can be evaluated for a large number of different input parameter values, which makes it a valuable test problem for our interpolation method.…”
Section: B Realistic 1p-kmc Based Datamentioning
confidence: 91%
“…III B 2, we needed 10 000 results for reference, which with more complex multi-species models could cost vast amounts of computational time. On the other hand, the RuO 2 CO oxidation model has been characterized in detail both in (p CO , p O 2 , T )-space 40,[46][47][48][49] and in rate constant space [42][43][44] and its behavior is well understood. This makes it ideal for testing new theoretical developments such as the one presented here.…”
Section: B Realistic 1p-kmc Based Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A positive (negative) DRC signifies that the reaction rate will increase (decrease) when increasing k I , whereas a value of zero signifies that the reaction rate is insensitive to variations in k I . The DRCs follow a sum rule, which states that the sum of all DRCs is equal to one (Meskine et al, 2009; Hoffmann et al, 2017). A single non-zero DRC equal to one then signifies a single rate-limiting step in the reaction mechanism, while in general several steps can be rate-limiting at the same time.…”
Section: Sensitivity Analysis and Uncertainty Quantificationmentioning
confidence: 99%
“…Relying instead on a finite-difference sampling, very long simulation times are typically required to reduce the statistical error sufficiently (Meskine et al, 2009). A more efficient three-stage approach has recently been proposed (Hoffmann et al, 2017), which allows for the direct sampling of sensitivity measures from a single KMC trajectory.…”
Section: Sensitivity Analysis and Uncertainty Quantificationmentioning
confidence: 99%